Efisiensi Pemupukan Tembakau melalui Inovasi Alat Penabur Pupuk PVC - Ardian Hudi Ramadhani; Diajeng Rizawati; Ulyn Nuha; Angelica Al'maliki Saliha; Shenda Amalia; Afiv Wahyudi (Lembaga Pengembangan Kinerja Dosen, 2025)
Appropriate technology innovation (TTG) in agriculture is an important solution in improving farmers' work efficiency, especially in the fertilization process. In Pamotan Village, where the majority of the population are tobacco farmers, the fertilization method is still done manually by sowing on the soil surface. This method often causes uneven distribution of fertilizer, wastage of energy and time, and a lot of fertilizer lost by water or wind. This community service activity aims to introduce a manual fertilizer sowing tool made from PVC as a simple, cheap, and easy-to-use solution for farmers. The implementation method includes counseling, tool demonstration, and direct training to farmer groups as activity partners. Evaluation was conducted through observation and questionnaires before and after the activity. The results showed an increase in farmers' understanding of efficient fertilization, as well as a positive response to the tools that were considered practical and economical. The use of this seedling tool can save up to 30% fertilizer and speed up the fertilization process by 40%. Thus, this manual fertilizer seedling tool is effective in helping farmers improve work efficiency and productivity, and is very suitable for small-scale farmers in rural areas.